The Essence of Trancendent Accountability Based on Tri Hita Karana in Desa Adat Penglipuran - I Made Putra Arya Wibawa; Bonnie Soeherman (Politeknik Ganesha Medan, 2025)
Accountability plays a crucial role and is applied in almost all types of organizations, whether profit-oriented or social organizations. However, the application of accountability in organizations that combine social, financial, and cultural aspects, such as Desa Adat Penglipuran, demonstrates different needs and focuses. This study highlights the unique concept of accountability in Desa Adat Penglipuran, which is expected to be replicated by other village organizations, particularly in Indonesia, thereby contributing both practically and theoretically. Using a qualitative approach and data collection methods, including interviews, observations, and document analysis, this study reveals that accountability in Desa Adat Penglipuran is understood by the community as a form of devotion and service to ancestors and God, in line with the characteristics of transcendent accountability. Local wisdom, such as Tri Hita Karana and Tri Mandala, plays a role in raising awareness among the community about the importance of balancing spiritual and financial factors in preserving village traditions. The construction of the transcendent accountability concept based on Tri Hita Karana creates more holistic understanding of transcendent accountability, which is capable of balancing financial and non-financial factors.